A Transfer Method for High‐Mobility, Bias‐Stable, and Flexible Organic Field‐Effect Transistors. Issue 5 (13th April 2020) - Peng, Boyu; Ji, Xudong; Jiao, Xuechen; Chu, Ming; Liu, Jinyu; Li, Yang; Chen, Ming; Zhou, Zhiwen; Zhang, Cuiping; Miao, Qian; Dong, Huanli; Huang, Baoling; et al.
Abstract: Substrates are crucial to the growth of organic semiconductor thin films and crystals, and thus the performance of the organic field‐effect transistors. To date, there has been no single substrate that can fulfill the demand for low‐voltage operation, large‐area crystal growth, bias stress stability, and mechanical flexibility at the same time. Here, a novel transfer method is reported, which separates the growth of the organic semiconductor active layers and the rest of the fabrication steps of the field‐effect transistors, so that high‐mobility active layers and bias‐stable dielectric substrates are combined. With the proposed transfer method, both vacuum sublimated thin films and solution‐processed crystals show remarkable improvement in the bias stability. With the high‐k dielectric and ultraflexible substrate, the device can operate at 2 V and shows no degradation in the carrier mobility when the bending radius is down to 215 mm. It is believed that this transfer method can advance the fabrication techniques of high‐performance organic field‐effect transistors, especially for their conformal or ultraflexible applications. Abstract : A novel transfer method for organic semiconductor is developed, allowing high‐mobility films and crystals to be combined with bias‐stable and low operating power flexible substrate. The transfer method is combined with photolithography on ultraflexible substrates to develop high‐precision active matrix that works under bending radius down to 215 µm.